PENGARUH FAKTOR KEUANGAN TERHADAP PERINGKAT OBLIGASI PADA PERUSAHAAN PERBANKAN - Davin Maverik; Susanto Salim (Jurnal Paradigma Akuntansi, 2026)
This study aims to determine the effect of financial factors on bond ratings of banking companies listed on the Indonesia Stock Exchange in 2018-2021. A total of 64 samples of banking sector company data during 2018-2021 were taken using a purposive sampling technique. The tool used for data calculation in this study is EViews 12. The results of the independent variable research obtained in this study reveal that leverage has a significant negative effect, liquidity and profitability have a not significant positive effect on bond ratings.